Corporate governance and earnings management: the role of board of directors and audit committee in financially distressed firms / Emita W. Astami and Rusmin Rusmin - Astami, Emita W; Rusmin, Rusmin (Universiti Teknologi MARA Cawangan Sarawak, 2018)
This study investigates the association between corporate governance and earnings management practices of Australian's financially distressed firms. Based on a sample of 164 firm-year incorporating non-financial firms experiencing financial distress, the cross-sectional modified Jones (1991) model is used to measure discretionary accruals (the proxy for earnings management). Board of directors and audit committee characteristic variables are employed as the key predictor variables for measuring the effectiveness of corporate governance. This study finds that the companies are seeking to reduce their reported earnings to increase the likelihood of making a profit in the following year with the goal of avoiding bankruptcy; a larger number of directors on a board is less effective in detecting and constraining the practices of earnings management by managers of distressed firms; an active audit committee plays a positive role in detecting and reducing the probability of earnings management. The findings of this study have implications especially to regulators and corporate governance reformists that determine corporate governance rules. This is primarily in regard to the efforts made by listed companies in maintaining their sustainability through more emphases on the process for monitoring and selection of board of directors and audit committee members to reinforce effectiveness in managerial performance evaluation.